Metodologias para evaluar la aplicacion de criterios e indicadores en el manejo forestal de bosques tropicales en America Latina - Pokorny, B.; Sabogal, C.; Camino, Ronnie de (2001)
Criteria and indicators to evaluate forest management (C&I) facilitate the understanding of and communication about sustainability. Thus an increasing number of national and international initiatives defined C&I sets for certification, monitoring and auditing of forest management. Because of the variety of C&I applications and the heterogeneity of C&I users, the demands and requirements on C&I in relation to application, evaluation and interpretation are diverse. To ensure viability and acceptance of C&I based forest management tools, this diversity has to be considered in the process of developing C&I sets. Based on a revision of C&I initiatives in Latin America, experiences made by the Center for International Forestry Research (CIFOR) and consultations with experts, the paper identifies and discusses the demands and requirements related to the application of C&I and its practical implications.